EFEKTIVITAS TIMBANG TERIMA METODE SBAR TERHADAP MUTU ASUHAN KEPERAWATAN - Rusdi Rusdi (Jurnal Medika : Karya Ilmiah Kesehatan, 2019)
Background: Patients’ handover with SBAR method is one of the indicators in the patient safety target, yet at Dirgahayu Hospital data shows that to achieve effective communication: SBAR in the medical surgery ward for the January to September 2018 period is only 80% - 90% and there are some incident findings including KTD 8 events, KNC 3 events, KPC 3 events. Objective: To find out the Effectiveness of Handover with SBAR Method to the Nursing Care Quality. Method: This study used a descriptive analytic design with cross sectional approach, which was conducted in December 2018 and the number of samples was 92 people selected by using the proportionate random sampling technique. Variable measurements were performed using questionnaires and observation sheets. Results: the effectiveness of handover with SBAR method to the quality of nursing care at Dirgahayu Samarinda Hospital is at ρ-value = 0.001. Conclusion: Patients’ handover with SBAR method greatly influences the safety of patients in hospitals, so that it can improve the quality of nursing care.